Effects of Lifting Height, Twist Angle and Load mass on Psychophysical Experience, Muscle Activity and Heart Rate during Manual Lifting - Isa , Halim; Seri Rahayu , Kamat; Syed mohamed, Muhammad syafiq; Mohd Shahrizan, Othman; Rohana , Abdullah (Trans Tech Publications, Switzerland, 2013)
In industry, manual lifting still a prevalent choice even though mechanized and automated equipment are provided. Mismatch between workers' capability and lifting height, twist angle, and load mass in manual lifting can contribute to occupational injuries such as back pain. The purpose of this study is to investigate the effects of lifting height, twist angle, and load mass on psychophysical experience, muscle activity, and heart rate while performing manual lifting activities. Subjective method associated with Likert Scale was applied to assess the psychophysical experience. Meanwhile, surface Electromyography and heart rate monitor were utilized to measure the muscle activity and heart rate respectively. Main findings of this study show that the rating of psychophysical experience, muscle activity, and heart rate increased when the lifting height and load mass increased. This study concluded that the psychophysical experience and muscle activity were affected when the lifting height, twist angle, and load mass were set at maximum level.